2014
DOI: 10.1080/21650020.2014.935467
|View full text |Cite
|
Sign up to set email alerts
|

Occupants housing satisfaction: does age really matter?

Abstract: Scholars from diverse disciplines have established how objective and subjective housing attributes influence occupants' housing satisfaction. The aim of this study is to determine the effect of age grouping on overall housing satisfaction with respect to private housing development in Abuja, Nigeria. Samples of 112 structured questionnaires were systematically administered to the occupants of Prince and Princes Housing Estate. Sixty-six were subsequently retrieved for analysis representing 74% response rate. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
(68 reference statements)
1
9
0
Order By: Relevance
“…Consistently with other studies (Nygren, 2007;Waziri, 2014) we found that housing attributes influence life satisfaction. In fact, a poorly equipped house showed to have a negative impact on life satisfaction.…”
Section: Discussionsupporting
confidence: 81%
“…Consistently with other studies (Nygren, 2007;Waziri, 2014) we found that housing attributes influence life satisfaction. In fact, a poorly equipped house showed to have a negative impact on life satisfaction.…”
Section: Discussionsupporting
confidence: 81%
“…The tenant subsystem comprises personal characteristics of residents commonly operationalised along demographic and socioeconomic status (SES) variables. These are gender, age, marital status, education, length of residency, tenure, household size, income and typology (Ibem et al, 2018;Makinde, 2015;Waziri et al, 2014). The dwelling system is often unbundled as housing features and services.…”
Section: Residential Satisfaction Based On Housing Habitability System Frameworkmentioning
confidence: 99%
“…The availability of amenities, facilities and services in proximity of a dwelling is yet another factor of residential satisfaction (Waziri, et al, 2014). The factors studied in this context include: local employment opportunities, the efficiency of public transport and access to recreational areas (Balestra & Sultan, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%